Spontaneous magnetization above T-C in polycrystalline La0.7Ca0.3MnO3 and La0.7Ba0.3MnO3 - Turcaud, J. A. (2017)
In the present work, spontaneous magnetization is observed in the inverse magnetic susceptibility of La0.7Ca0.3MnO3 and La0.7Ba0.3MnO3 compounds above T-C up to a temperature T*. From information gathered from neutron diffraction, dilatometry, and high-field magnetization data, we suggest that T* is related to the transition temperature of the low-temperature (high magnetic field) magnetic phase. In the temperature region between T* and T-C, the application of a magnetic field drives the system from the high-temperature to low-temperature magnetic phases, the latter possessing a higher magnetization.